2010
DOI: 10.1016/j.cub.2009.11.050
|View full text |Cite
|
Sign up to set email alerts
|

The Evolution of Human Genetic and Phenotypic Variation in Africa

Abstract: Africa is the birthplace of modern humans, and is the source of the geographic expansion of ancestral populations into other regions of the world. Indigenous Africans are characterized by high levels of genetic diversity within and between populations. The pattern of genetic variation in these populations has been shaped by demographic events occurring over the last 200,000 years. The dramatic variation in climate, diet, and exposure to infectious disease across the continent has also resulted in novel genetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
113
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(120 citation statements)
references
References 77 publications
4
113
0
3
Order By: Relevance
“…Despite both archaeological (27,28) and genetic evidence (28)(29)(30)(31)(32) for ancient population structure in Africa, none of the genetic models used so far to study the geographic patterns of similarity has incorporated structure in Africa. Currat and Excoffier (5) used a spatial framework to investigate admixture with Neanderthals, but concentrated on the role of gene surfing during the expansion wave in affecting the distribution of polymorphisms unique to Neanderthals across Eurasia, provided admixture did happen.…”
mentioning
confidence: 99%
“…Despite both archaeological (27,28) and genetic evidence (28)(29)(30)(31)(32) for ancient population structure in Africa, none of the genetic models used so far to study the geographic patterns of similarity has incorporated structure in Africa. Currat and Excoffier (5) used a spatial framework to investigate admixture with Neanderthals, but concentrated on the role of gene surfing during the expansion wave in affecting the distribution of polymorphisms unique to Neanderthals across Eurasia, provided admixture did happen.…”
mentioning
confidence: 99%
“…Previous studies (Voight et al 2006;Sabeti et al 2007;Jarvis et al 2012;Lachance et al 2012) have reported strong signals of positive selection in African populations. Local adaptation is expected to be common within Africa, as African populations practice a range of subsistence strategies and inhabit diverse environments to which adaptation may have occurred (deMenocal 2004;Campbell and Tishkoff 2010;deMenocal 2011). Selection may also have acted more efficiently in African populations, many of which have maintained large effective population sizes for the past 50,000 years, in contrast to populations outside of Africa (Tenesa et al 2007;Lambert and Tishkoff 2009;Campbell and Tishkoff 2010;Henn et al 2011).…”
mentioning
confidence: 99%
“…Local adaptation is expected to be common within Africa, as African populations practice a range of subsistence strategies and inhabit diverse environments to which adaptation may have occurred (deMenocal 2004;Campbell and Tishkoff 2010;deMenocal 2011). Selection may also have acted more efficiently in African populations, many of which have maintained large effective population sizes for the past 50,000 years, in contrast to populations outside of Africa (Tenesa et al 2007;Lambert and Tishkoff 2009;Campbell and Tishkoff 2010;Henn et al 2011). While African populations would appear ideal for understanding the extent of positive selection in humans, they have usually been underrepresented in such studies.…”
mentioning
confidence: 99%
“…African pygmies share roots at the base of human history with Khoisan and Hadza (Henn et al 2011;Verdu and Destro-Bisol 2012) but exhibit distinct polymorphisms associated with immune function, metabolism, growth, and skeletal turnover, critical for lacta-tion (Campbell and Tishkoff 2010;Mendizabal et al 2012;Schuh-Huerta and Pera 2011). Less apparent is the phylogenetic, ecological, and cultural diversity of pygmies (Bahuchet 2012;Hewlett 1996), as eastern (e.g., Efé, Mbuti) and western (e.g., Aka, Bofi) populations diverged with fragmentation of Congo forests around 27,000 BP, with little subsequent admixture between them (Batini et al 2011).…”
Section: Allonursing As Preventative Medicinementioning
confidence: 99%